Impact of Road Infrastructure to Market Access and Income Generating Opportunities of Rural Area in Mahottari District of Nepal - Yadav, Bhagu; Dahal, Madhav Prasad (NPRC Journal of Multidisciplinary Research, 2026)
Background: Road infrastructure is the backbone of rural as well as urban transport systems. The road infrastructure plays a critical impact in the rural areas for market access and improving their livelihoods. In Mahottari district of Nepal, more rural road infrastructure is upgraded from different agency between 2016 and 2024.Objective: The objective of this study is to examine the impact of road infrastructure in market access and income-generating opportunities for rural households in Mahottari District.Methodology: The overall strategy is pragmatic combining deductive (QUAN) and inductive (QUAL). The study follows a mixed method approach to understand the impact of road infrastructure in rural livelihoods. Questionnaire survey of two hundred fourty households for three rural municipalities is for quantitative data collection. FGD with users as well as KIIs with rural municipality's president are the qualitative data collection.Findings: Improvements in the road infrastructure have facilitated market access by decreasing travel duration and transportation expenses. The households have reported receiving better prices for their goods and have gained improved access to inputs and services, resulting in increased incomes. The research indicated that rural roads allowed households to transition from exclusively subsistence farming to a variety of income-generating type activities, including small enterprises, wage employment, and transport services.Conclusion: Road infrastructure has improved access to both local and regional markets, allowing the farmers and entrepreneurs to enhance their incomes by lowering transaction costs and time. The research findings regarding the impact of road infrastructure on the livelihoods of rural people in the Mahottari district clearly indicate that the development of rural roads has positively influenced livelihood better in rural area. The households have reported an increase in occupational diversity, which includes participation in non-farm employment, small-scale trade as well as transport services.